A comprehensive review on ethnopharmacological, phytochemical, pharmacological and toxicological evaluation, and quality control of Pinellia ternata (Thunb.) Breit. (15th November 2022) - Bai, Jing; Qi, Jianbo; Yang, Li; Wang, Zhengtao; Wang, Rui; Shi, Yanhong
Abstract: Ethnopharmacological relevance: Pinellia ternata tuber (PTT), the dried tuber of Pinellia ternata (Thunb.) Breit., has a long history of use in traditional Chinese medicine for drying dampness, resolving phlegm, down-bearing counterflow to check vomiting and dissipating masses. Modern pharmacology studies have revealed that PTT has diverse pharmacological effects such as antitussive and expectorant, anti-emetic, anti-tumor, and anti-inflammatory effect, etc. Aim of the review: This review aims to provide a critical and comprehensive evaluation on ethnopharmacological uses, chemical constituents, pharmacological and toxicological effects, analytical methods and quality control of PTT, which would provide scientific evidence for exploring future therapeutic, and formulating quality and safety criteria of PTT. Materials and methods: Pertinent information was systematically collected from several electronic scientific databases including Web of Science, Science Direct, PubMed, Elsevier, Wiley Online Library and China national knowledge infrastructure (CNKI), as well as the classic Chinese medical books. Results: PTT is reported to be widely used traditionally for the treatment of cough, vomiting, infection, and inflammatory diseases in many southeast Asian countries. Phytochemical studies have revealed the presence of a total of 233 compounds belonging to alkaloids, nucleosides, organic acids, polysaccharides, volatile oils, amino acids, proteins, starches, etc. The extracts and components of PTT have possessed diverse pharmacological activities, such as antitussive, antiemetic, antitumor, antibacterial, and sedative-hypnotic activities. Raw P. ternata tuber (RPTT) with a pungent taste causes acrid irritation of the oral and laryngopharynx mucosa when taken by mistake, while its toxicity and side effects of RPTT can be dramatically reduced with proper processing. Three kinds of processed P. ternata tuber with different processing methods are available and traded in market, as well as applied in clinical treatments. Additionally, although raw or processed PTT have been recorded in several mainstream pharmacopoeias such as Chinese Pharmacopoeia, Japanese Pharmacopoeia, and Korean Pharmacopoeia, the quality items and requirements varies a lot. Therefore, a unified international standard of raw and processed PTT is urgent need to be done. Conclusions: The ethnopharmacological, phytochemical, pharmacological and toxicological and quality evaluation of PTT were highlighted in this review, which provides potential reference information to future investigate and commercially explore for pharmaceutical applications. Nevertheless, an efficient method for chemical profiling is still unavailable to find potent bioactive markers for quality control, and then comprehensive pharmacological effects and mechanisms and toxicological evaluation of PTT require further detailed research to ensure their quality and safety. Graphical abstract: Image 1 Highlights: This is the first review to comprehensively summarize the traditional uses, phytochemistry, pharmacological effects, toxicity and quality evaluation of Pinellia ternata (Thunb.) Breit. A total of 233 compounds belonging to different chemical classes were isolated from PTT. Analytical methods and quality control of PTT were discussed in detail.